Medical Therapy and Ruqyah in The Treatment of Schizophrenia: A Perspective of Islamic Law and Health Regulation in Indonesia - Rachman, Lyvia Aulia; Fieneyantie, Fatyah; Aprilia, Sandini; Amalia, Septy; Karunia, Suci; Faozi, Akhmad; Supriyadi, Tedi (Teunuleh Publisher, 2025)
Schizophrenia is a serious mental disorder characterized by perceptual, thought, and behavioral disorders. In societies with strong religious backgrounds, many view this disorder as the result of spiritual disorders, preferring ruqyah therapy to medical treatment. This study aims to explore and compare the effectiveness of medical therapy and ruqyah therapy in the treatment of schizophrenia, as well as to understand the public's perception of the two approaches. The method used was qualitative research with a phenomenological approach, through in-depth interviews with eight participants consisting of medical personnel and scholars in the Sumedang area. The results of the study show that medical therapy remains the main cornerstone in controlling the symptoms of schizophrenia, especially through the use of antipsychotics. However, ruqyah therapy provides positive psychological effects such as calmness and increased spiritual spirit of the patient, and is often chosen because it is considered more in accordance with religious values. The integration between medical and spiritual approaches is seen as a holistic strategy, especially in the context of Muslim society. The study also highlights the importance of the role of family, community education, and stigma reduction in supporting therapy success. In conclusion, an integrative approach that includes medical and spiritual therapies can improve patient adherence, reduce stigma, and strengthen social support in schizophrenia recovery.